Creatine supplementation reduces the cerebral oxidative and metabolic stress responses to acute in utero hypoxia in the late‐gestation fetal sheep. (3rd June 2022) - Tran, Nhi Thao; Kowalski, Greg M.; Muccini, Anna M.; Nitsos, Ilias; Hale, Nadia; Snow, Rod J.; Walker, David W.; Ellery, Stacey J.
Abstract : Abstract: Prophylactic creatine treatment may reduce hypoxic brain injury due to its ability to sustain intracellular ATP levels thereby reducing oxidative and metabolic stress responses during oxygen deprivation. Using microdialysis, we investigated the real‐time in vivo effects of fetal creatine supplementation on cerebral metabolism following acute in utero hypoxia caused by umbilical cord occlusion (UCO). Fetal sheep (118 days' gestational age (dGA)) were implanted with an inflatable Silastic cuff around the umbilical cord and a microdialysis probe inserted into the right cerebral hemisphere for interstitial fluid sampling. Creatine (6 mg kg −1 h −1 ) or saline was continuously infused intravenously from 122 dGA. At 131 dGA, a 10 min UCO was induced. Hourly microdialysis samples were obtained from −24 to 72 h post‐UCO and analysed for percentage change of hydroxyl radicals ( OH) and interstitial metabolites (lactate, pyruvate, glutamate, glycerol, glycine). Histochemical markers of protein and lipid oxidation were assessed at post‐mortem 72 h post‐UCO. Prior to UCO, creatine treatment reduced pyruvate and glycerol concentrations in the microdialysate outflow. Creatine treatment reduced interstitial cerebral OH outflow 0 to 24 h post‐UCO. Fetuses with higher arterial creatine concentrations before UCO presented with reduced levels of hypoxaemia ( P O 2 P_O_2 and S O 2 S_O_2 ) during UCO which associated with reduced interstitial cerebral pyruvate, lactate and OH accumulation. No effects of creatine treatment on immunohistochemical markers of oxidative stress were found. In conclusion, fetal creatine treatment decreased cerebral outflow of OH and was associated with an improvement in cerebral bioenergetics following acute hypoxia. Key points: Fetal hypoxia can cause persistent metabolic and oxidative stress responses that disturb energy homeostasis in the brain. Creatine in its phosphorylated form is an endogenous phosphagen; therefore, supplementation is a proposed prophylactic treatment for fetal hypoxia. Fetal sheep instrumented with a cerebral microdialysis probe were continuously infused with or without creatine‐monohydrate for 10 days before induction of 10 min umbilical cord occlusion (UCO; 131 days' gestation). Cerebral interstitial fluid was collected up to 72 h following UCO. Prior to UCO, fetal creatine supplementation reduced interstitial cerebral pyruvate and glycerol concentrations. Fetal creatine supplementation reduced cerebral hydroxyl radical efflux up to 24 h post‐UCO. Fetuses with higher arterial creatine concentrations before UCO and reduced levels of systemic hypoxaemia during UCO were associated with reduced cerebral interstitial pyruvate, lactate and OH following UCO. Creatine supplementation leads to some improvements in cerebral bioenergetics following in utero acute hypoxia. Abstract : Abstract figure legend Prophylactic fetal creatine supplementation is a proposed treatment strategy for acute transient asphyxia such as umbilical cord occlusion (UCO). Fetal sheep with higher circulating arterial creatine (Cr) concentrations before UCO and reduced levels of systemic hypoxaemia during UCO were associated with reduced accumulation of cerebral interstitial pyruvate (Pyr), lactate (Lac) and reactive oxygen species (specifically OH) following UCO as measured by microdialysis. There are three proposed mechanisms, which include maintaining ATP turnover during hypoxia and therefore reducing the need for aerobic metabolism, anaerobic processes, and active reactive oxygen species scavenging. Created with BioRender.com.